TETANUS IN SHEEP OF AN ORGANIZED LIVESTOCK FARM - A CASE REPORT - Muralidharan, J; Ramesh, V; Saravanan, S; Kumar , V Ramesh Saravana (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
Tetanus (lockjaw) caused by clostridium tetani is a life threatening disease that affects all domestic animals and humans worldwide. Because of its low frequency of occurrence, this sporadic disease attracts little concern from the sheep industry. It is usually seen in lambs less than six months of age. However, the farm flocks experience a higher incidence because sheep occupy spore seeded pens following docking, castration, tagging, shearing and lambing. Spores of this bacterium can be found in faeces and soil ,producing a powerful toxin in open wounds, which is not destroyed by disinfectants. Treatment of clinical cases is costly, may not be successful and in most instances the animals are often found dead. This paper reports tetanus in an adult sheep from an organized sheep farm maintained along with other livestock species viz, goat, horse and cattle, under hygienic environment.
Keywords: SHEEP; ORGANIZED LIVESTOCK FARM; TETANUS